'Heroa' and the city. Kuprlli's new architecture and the making of the 'Lycian acropolis' of Xanthus in the early Classical period. (6th July 2015) - Draycott, Catherine M.
Abstract: This paper considers the architectural design of a group of three buildings erected on what is commonly called the 'acropolis' of Xanthus in Lycia in the second quarter of the fifth century BC – a time of increasing social, political and economic complexity in this corner of the Aegean/eastern Mediterranean. Although, as the first examples of stone imitations of timber architecture, these buildings are often mentioned in discussions about the origins of Lycian 'house tombs' and sometimes summarily discussed in terms of their function, the architectural phenomenon that these buildings represent has not received extensive consideration. Here it is argued that their genesis can be located in the building of a monumentalised skyline, potentially drawing on other cities' acropoleis as models. In addition to this, the buildings also represent quite new commemorative practices. It is proposed that these three innovative structures could be related to a broader practice of erecting monuments to honour city founders in prominent public spaces. In this way, both the terms 'acropolis' and 'heroa' – loaded terms usually only loosely applied in the literature on these monuments – may be useful for capturing the peculiar qualities of the architectural projects that transformed Kuprlli's Xanthus.